The Role of Game Folklore in Children's Life - Ruziboyeva Madina Salimovna (Zien Journals, 2023)
Collecting and studying the wealth of creativity created by the Uzbek people for thousands of years, passed down from generation to generation, raising the young generation to be spiritually rich, morally pure, and physically fit on the basis of these rich treasures is one of the urgent issues of today
Keywords: Uzbek folk games; game rules; examples of folklore; pedagogical value of games